Suplementação com farelo de arroz integral e/ou gordura protegida na recria de novilhas de corte em pastagem de aveia-preta e azevém - Pizzuti, Luiz Angelo Damian (2011)
The objective of the present study was to evaluate the reflection of supplementation with integral rice bran and/or protected fat in the productive parameters of oat and ryegrass pasture and in the development, reproductive performance and behavior of beef heifers. Twenty-eight heifers, Charolais x Nellore crossbred, with initial average age of 18 moths and initial average weight of 274.9 kg, were distributed into four treatments with three repetitions per area. The animals were kept in oat + ryegrass pasture and distributed into the following treatments: Without supplementation (SS): heifers kept in pasture; Megalac (MEG): supplementation with protected fat; Integral rice bran (FAI): supplementation with integral rice bran; FAI+MEG: supplementation with integral rice bran + protected fat. The pasture intake increased throughout the periods (Y=2.71542+.01665*Day; P=.0023). The animal stocking, stocking rate, loss of forage and pasture intake weren´t influenced by treatments (P>.05). Body condition of heifers increased linearly .012 points every day, correlating positively with the final weight (r=.79; P<.0001). The greatest daily weight gain, 1.395 kg, occurred at the first period and when animals were supplemented with FAI+MEG. At the last period, animals from SS treatment had the lowest daily weight gain, .888 kg. Neutral detergent fiber intake increased linearly .045 kg per day (P<.05) during grazing periods. The supplementation with FAI and FAI+MEG reduced the time spent by heifers with grazing, 49.63%, in relation to animals from SS and MEG treatments, 63.13%. The feeding stations per minute had an increase during grazing periods due to the reduction in time spent in each feeding station and the linear decrease of bit number per feeding station (P<.05), the latter ranging 34.48% lower at the final of grazing period. The supplementation of beef heifers with integral rice bran and/or protected fat doesn‟t alter productive parameters of oat and ryegrass pasture, neither pasture intake and total dry matter intake. Increases in daily accumulation of dry matter and feeding conversion promoted an increase in forage losses. The average daily weight gain is not changed by the supplementation. The use of pasture of temperate climate, supplemented or not, promotes adequate structural and reproductive development of the heifers, given benefiting the zootecnic indices at the first mating at 25/27 months of age. The heifers supplemented with FAI and FAI+MEG require less time for activities of grazing seizure. Grazing and idle times don‟t change with periods of grazing, however rumination time grows with the increase of neutral detergent fiber intake.